Research on the comprehensive evaluation of the value of water conservancy heritage based on expert knowledge and public cognition: a case study of Red Flag Canal - Yanrong Wang; Hao Fu; Shujing Zhang; Nilupa Jiapaer (Water Policy, 2022)
The scientific construction of the indicator system and the objective evaluation method that apply to the value of water conservancy heritage are of great significance to the promotion and development of water culture and water conservancy heritage conservation. This study constructs an index system for water conservancy heritage value assessment from seven first-level indexes, such as engineering value, economic value, social value, ecological value, artistic value, innovative value and heritage value, builds a fuzzy comprehensive evaluation model based on expert knowledge and public perception and carries out empirical evidence with the example of China's Red Flag Canal. The results show that the overall value of the Red Flag Canal was 94.68 points, which reached a high level. The result is consistent with that the Red Flag Canal was successfully declared as the national water conservancy heritage, thus verifying the scientificity and rationality of the index system and the evaluation method constructed by this study. HIGHLIGHTS This study constructs the first-level and second-level index systems for the comprehensive evaluation of the value of water conservancy heritage.; This study builds a comprehensive evaluation model based on expert knowledge and public cognition.; This study conducts a comprehensive evaluation of the value of water conservancy heritage.;